2015
DOI: 10.1016/j.jsps.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Penetration enhancers in proniosomes as a new strategy for enhanced transdermal drug delivery

Abstract: The aim of this work is to investigate penetration enhancers in proniosomes as a transdermal delivery system for nisoldipine. This was performed with the goal of optimising the composition of proniosomes as transdermal drug delivery systems. Plain proniosomes comprising sorbitan monostearate, cholesterol, ethanol and a small quantity of water were initially prepared. Subsequently, proniosomes containing lecithin or skin penetration enhancers were prepared and evaluated for transdermal delivery of nisoldipine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Furthermore, low cost, more stability, entrapping of more substances, ease of handling, ease of formulation and storage, less prone to oxidation and availability of prepared materials in pure form exploit them a propitious drug delivery system, and superior to liposomes (Paecharoenchai et al, 2013;Zaki Ahmad et al, 2014). Niosomes also undergo fusion, aggregation, sedimentation, leakage of entrapped drugs on storage, and loss of vesicular integrity thus, limiting their shelf life (El-Laithy et al, 2011;Shaker et al, 2013;El Maghraby et al, 2015;Madan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, low cost, more stability, entrapping of more substances, ease of handling, ease of formulation and storage, less prone to oxidation and availability of prepared materials in pure form exploit them a propitious drug delivery system, and superior to liposomes (Paecharoenchai et al, 2013;Zaki Ahmad et al, 2014). Niosomes also undergo fusion, aggregation, sedimentation, leakage of entrapped drugs on storage, and loss of vesicular integrity thus, limiting their shelf life (El-Laithy et al, 2011;Shaker et al, 2013;El Maghraby et al, 2015;Madan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…After hydration, the solution was sonicated in an ultrasonic probe for at least 3 min to prepare the DFO encapsulated PEGylated nano‐niosome. A predetermined amount of the drug was added to the previously prepared solution, which was then processed as mentioned above …”
Section: Methodsmentioning
confidence: 99%
“…The most widely investigated permeation enhancer is oleic acid, an FDA approved, monostructured fatty acid and membrane fluidizing agent. Several studies have suggested that oleic acid can stimulate the lipid bilayer of stratum corneum of skin, hence, the modification of nanoparticles with oleic acid can open the channels in the stratum corneum and thereby enhance the permeation of macromolecules into the deeper layer of the skin (30,31). In the current study, we have used two permeation enhancers, viz.…”
Section: Analysis Of Drug Permeation Through Skinmentioning
confidence: 99%